2011
DOI: 10.1351/pac-rep-10-07-02
|View full text |Cite
|
Sign up to set email alerts
|

State diagrams for improving processing and storage of foods, biological materials, and pharmaceuticals (IUPAC Technical Report)

Abstract: Supplemented temperature/composition phase diagrams include the non-equilibrium glass-transition temperature (T g ) curve and equilibrium ice-melting and solubility curves. The inclusion of the non-equilibrium curve allows one to establish relationships with the time coordinate and, thus, with the dynamic behavior of systems, provided that the thermal history of such systems is known.The objective of this report is to contribute to the potential applications of supplemented state diagrams for aqueous glass-for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 256 publications
(504 reference statements)
1
23
0
Order By: Relevance
“…The temperature at which this transition occurs is well known as the glass transition temperature or simply Tg (Rhaman, 2010;Roos, 2010;Sablani et al, 2010). In recent years, the study of the relationship between Tg and water mass fraction (x w ) or solid mass fraction (x s ) has received considerable attention and is useful for construction of simplified stability/ mobility diagrams or supplemented state diagrams of several sugar-rich products, such as dried fruit and fruit juice powders (Rahman, 2006;Jaya and Das, 2009;Rhaman, 2010;Roos, 2010;Sablani et al, 2010;Buera et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The temperature at which this transition occurs is well known as the glass transition temperature or simply Tg (Rhaman, 2010;Roos, 2010;Sablani et al, 2010). In recent years, the study of the relationship between Tg and water mass fraction (x w ) or solid mass fraction (x s ) has received considerable attention and is useful for construction of simplified stability/ mobility diagrams or supplemented state diagrams of several sugar-rich products, such as dried fruit and fruit juice powders (Rahman, 2006;Jaya and Das, 2009;Rhaman, 2010;Roos, 2010;Sablani et al, 2010;Buera et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The process emphasizes the glass-forming characteristics of carbohydrates at low water contents and temperatures, while viscous flow required for structure formation can be achieved as a result of thermal and water plasticization above the glass transition of the solids [21]. The recognition of the underlying materials science principles was described successfully by state diagrams for dehydration, extrusion and freezing [4,5,23,24].…”
Section: Food Processing and Food Structurementioning
confidence: 99%
“…Theories of water activity as a mobility-controlling factor were complemented by information on the glass transition of particular food components at various levels of water plasticization [2,5]. The effects of the glass transition on oxidation, nonenzymatic browning reactions, enzymatic reactions, structural collapse and component crystallization have shown that glass transition affects and often explains the occurrence of such reactions although may not be sufficient as such to explain temperature dependence of deteriorative changes in foods [24].…”
Section: Food Processing and Food Structurementioning
confidence: 99%
“…It assists in predicting the physical and chemical changes in foods during processing and storage. A growing number of studies have been conducted on different kinds of foods; however, these studies mainly focused on fruit, vegetables, and biomaterials . The state diagrams of rice, brown rice, potato starch, and extruded instant artificial rice have been reported.…”
Section: Introductionmentioning
confidence: 99%